Nursing Care For Preeclampsia in Pregnant Women With Warm Water Foot Bath Hydrotherapy Interventions - Ima Sukmawati; Neng Fitri (LPPM STIKes Muhammadiyah Ciamis, 2023)
Preeclampsia is an increase in blood pressure which is usually one of the complications experienced by pregnant women, the accumulation of fluid in one of the tissues, hydrotherapy action is very suitable for use because it is more practical so that it can be done independently and does not have dangerous side effects, The purpose in this study is to be able to carry out nursing care comprehensively with pain clients with hydrotherapy soak using warm water The method of research is descriptive case study method, by managing one client using the nursing process approach. The resultse in the study The implementatin of the implementation was carried out for 3 days, with the provision of hydrotherapy soaking the feet using warm water very effectively given to clients with preeclampsia and complaining of pain The conclusion is that hydrotherapy using warm water is very effective given to pregnant women so that it can reduce the pain felt.